Identification of Barriers to Completion of Study for Physical Education Students - Henry Maksum; Muhammad Suhairi; Nevi Hardika; Zusyah Porja Daryanto; Mikkey Anggara Suganda (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to investigate the challenges faced by Physical Education students at a public university in Pontianak in successfully finishing their courses within the designated timeframe of four years or less. The nature of this research might be characterised as descriptive. The sample for this study consisted of 564 individuals who were enrolled as students in the Faculty of Sports and Health Education, specifically in the Physical Education study programme for the Bachelor programme for the academic years of 2019-2022. The sample in this study amounted to 164 people. Sampling withdrawal using random sampling. Data collection was carried out using a questionnaire distribution instrument with a Likert scale to respondents who had been assigned to the subject as the research sample. This study's factors and theoretical studies determine instrument arrangement. This study's factors are students, infrastructure and facilities, teaching staff (method, lecture atmosphere, guidance, material ready), faculty leader administration, and semester study load (credits). An instrument validity test was performed utilising a user test with 80% valid question items to determine measurement validity. Descriptive research results were obtained as follows, namely: (1) Students 59.18% sufficient category, (2) Infrastructure and facilities obtained 54.75% Enough category, (3) Teaching staff (method, lecture atmosphere, guidance, material readiness ) obtained 60.67 in the Good category, (4) administration of the faculty leadership obtained 60.67% in the Good category, and (5) Semester study load (credits) obtained 60.29% in the Good category. It can be interpreted that the five variables in the research results have an impact on the timely completion of learning for students of the Physical Education Study Program.